2004
DOI: 10.1007/s00424-003-1073-4
|View full text |Cite
|
Sign up to set email alerts
|

The SLC36 family: proton-coupled transporters for the absorption of selected amino acids from extracellular and intracellular proteolysis

Abstract: Whilst Na(+) has replaced H(+) as a major transport driving force at the plasma membrane of animal cells, the evolutionarily older H(+)-driven systems persist on endomembranes and at the plasma membrane of specialized cells. The first member of the SLC36 family, present in both intracellular and plasma membranes, was identified independently as a lysosomal amino acid transporter (LYAAT1) responsible for the export of lysosomal proteolysis products into the cytosol and as a proton/amino acid transporter (PAT1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 23 publications
1
72
0
Order By: Relevance
“…It is unclear whether such pH dependence reflects proton-nucleoside co-transport activity, such as is seen for kinetoplastid ENT family members (8). However, the optimum pH value corresponds to that of late endosomes/lysosomes and probably reflects an evolutionary adaptation to the acidic interior of these organelles: lysosomes are known to contain other proton-linked solute exporters, such as amino acid transporter LYAAT1/PAT1 (31). Previous studies of adenosine uptake into isolated rat liver lysosomes showed no similar dependence on the pH of the medium (29), but the dependence of activity on the intraorganelle pH was not studied.…”
Section: Fig 2 Subcellular Distribution Of Hent3 In Hela Cellsmentioning
confidence: 95%
“…It is unclear whether such pH dependence reflects proton-nucleoside co-transport activity, such as is seen for kinetoplastid ENT family members (8). However, the optimum pH value corresponds to that of late endosomes/lysosomes and probably reflects an evolutionary adaptation to the acidic interior of these organelles: lysosomes are known to contain other proton-linked solute exporters, such as amino acid transporter LYAAT1/PAT1 (31). Previous studies of adenosine uptake into isolated rat liver lysosomes showed no similar dependence on the pH of the medium (29), but the dependence of activity on the intraorganelle pH was not studied.…”
Section: Fig 2 Subcellular Distribution Of Hent3 In Hela Cellsmentioning
confidence: 95%
“…The PAT1 mRNA shows widespread expression with high levels in brain, intestine and kidney whereas the PAT2 mRNA is highly abundant in lung, kidney and brain. PAT3 mRNA is found solely in testis, whereas PAT4 mRNA shows ubiquitous expression [8].…”
mentioning
confidence: 99%
“…The PAT1 mRNA shows widespread expression with high levels in brain, intestine and kidney whereas the PAT2 mRNA is highly abundant in lung, kidney and brain. PAT3 mRNA is found solely in testis, whereas PAT4 mRNA shows ubiquitous expression [8].So far, only PAT1 and PAT2 have been characterized functionally. They have an exceptional position among the mammalian amino acid transporters, as they act as electrogenic amino acid/proton symporters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PAT3 and PAT4 are orphan transporters, whereas PAT1 (also designated as LYAAT1) and PAT2 are characterized as electrogenic amino acid/proton co-transporters with a high selectivity for amino acids with apolar and small side chains (3,16). PAT1 was shown to transport glycine, L-alanine, and L-proline as well as GABA and D-serine (11,12,(17)(18)(19).…”
mentioning
confidence: 99%